1999
DOI: 10.1159/000014569
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidant/Antioxidant Network: Role of Melatonin

Abstract: Melatonin is now known to be a multifaceted free radical scavenger and antioxidant. It detoxifies a variety of free radicals and reactive oxygen intermediates including the hydroxyl radical, peroxynitrite anion, singlet oxygen and nitric oxide. Additionally, it reportedly stimulates several antioxidative enzymes including glutathione peroxidase, glutathione reductase, glucose-6-phosphate dehydrogenase and superoxide dismutase; conversely, it inhibits a prooxidative enzyme, nitric oxide synthase. Melatonin also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(147 citation statements)
references
References 61 publications
4
138
0
5
Order By: Relevance
“…MLT also has substantial free radical scavenging/antioxidant and anticancer activity in experimental systems (45,60,61,63). This knowledge has obvious relevance to human health (22,26,54,60,61,66,79).…”
Section: Melatonin and Human Breast Cancer Cell Growthmentioning
confidence: 99%
“…MLT also has substantial free radical scavenging/antioxidant and anticancer activity in experimental systems (45,60,61,63). This knowledge has obvious relevance to human health (22,26,54,60,61,66,79).…”
Section: Melatonin and Human Breast Cancer Cell Growthmentioning
confidence: 99%
“…Êð³ì òîãî, â³í º äîñèòü åôåêòèâíèì àíòèîêñè-äàíòîì, ÿêèé ïîãëèíຠñèíãëåòíèé êèñåíü, ñóïåðîêñèäíèé àí³îí, ïåðîêñèí³òðèò ³ îêñèä àçîòó [24,26]. Ïðè öüîìó éîãî àêòèâí³ñòü í à á à ã à ò î á ³ ë ü ø à ï î ð ³ â í ÿ í î ç ³ í ø è ì è â³äîìèìè ñêàâåíäaeåðàìè â³ëüíèõ ðàäèêàë³â [24,25]. Àíòèîêñèäàíòí³ âëàñòèâîñò³ ìåëàòîí³íó ïðîÿâëÿþòüñÿ ³ â éîãî çäàòíîñò³ àêòèâóâàòè ôåðìåíòè ïåðåòâîðåííÿ ³íøîãî ïîòóaeíîãî àíòèîêñèäàíòà ãëóòàò³îíó [1,10], äåô³öèò ÿêîãî ïîêàçàíèé ïðè ÕÏ òà ³íøèõ ñòàíàõ ñòàíàõ, ïîâÿçàíèõ ç íåñòà-Ðèñ.…”
Section: ðåçóëüòàòè òà ¯õ îáãîâîðåííßunclassified
“…that result in changes in sleep and circadian biological rhythms. In some of these studies, in addition to sleep enhancements, the antioxidant properties of this hormone were the main reason for testing this pineal hormone (Reiter, 1998;Reiter et al, 1999;Reiter et al, 2000;Reiter et al, 2003). In a recent publication, Vankirk et al (2017), using a Drosophila model, demonstrated that injection of melatonin increases the regularity of heartbeat significantly, and it can rescue rhythmicity in flies bearing mutations that adversely affect cardiac function.…”
Section: Introductionmentioning
confidence: 99%